Blue Eagles and Deja Vu - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "Blue Eagles and Deja Vu," written by Walter B. Wriston for the Society of American Business Writers on 5 May 1975. The original speech is located in MS134.001.002.00034.